Cycling Athlete Performance: Analysis of Muscle Oxygen Saturation through Moxy Measurement - Jajat Darajat Kusumah Negara (Universitas Pendidikan Indonesia, 2023)
This study was aimed at conducting an analysis related to the performance of cyclists, namely the analysis of oxygen saturation in the muscles using muscle oxygen monitoring. This study used a single-subject design. Respondents of this study were road bike athletes preparing for multi-event competitions in West Java province. The measured data were related to oxygen saturation as measured by Moxy (Muscle Oxygen Monitoring), the tool used to examine how well our muscles use oxygen. The instruments included a smartwatch as an additional data collection tool and the Elevate Heart Rate sensor on the watch to record heart rate. The results found that the respondent muscle oxygen saturation was in the fairly good category for the female because the average result fell in the range of 70–80%, not much different from the starting point of the test. The analysis showed that there was a positive correlation between SmO2 and THb, where SmO2 gave a contribution of 61%. The result of this analysis is expected to be used as an evaluation for coaches in preparing athlete training programs.